Cytokinesis requires localized β-actin filament production by an actin isoform specific nucleator - A. Chen; Pamma D. Arora; Christopher A. McCulloch; Andrew Wilde (2017)
Cytokinesis is initiated by the localized assembly of the contractile ring, a dynamic actomyosin structure that generates a membrane furrow between the segregating chromosomal masses to divide a cell into two. Here we show that the stabilization and organization of the cytokinetic furrow is specifically dependent on localized β-actin filament assembly at the site of cytokinesis. β-actin filaments are assembled directly at the furrow by an anillin-dependent pathway that enhances RhoA-dependent activation of the formin DIAPH3, an actin nucleator. DIAPH3 specifically generates homopolymeric filaments of β-actin in vitro. By employing enhancers and activators, cells can achieve acute spatio-temporal control over isoform-specific actin arrays that are required for distinct cellular functions.